Survival Impact of Second-Line Immune Checkpoint Inhibitors in Older Patients With Advanced Squamous-Cell NSCLC: Post Hoc Analysis of the CAPITAL Study - Yoshihito Kogure, MD, PhD; Akiko Kada, MPH; Hiroya Hashimoto, PhD; Shinji Atagi, MD; Yuichi Takiguchi, MD; Hideo Saka, MD; Noriyuki Ebi, MD; Akira Inoue, MD; Takayasu Kurata, MD; Yuka Fujita, MD; Yoichi Nishii, MD; Hidetoshi Itani, MD; et al. (JTO Clinical and Research Reports, 2023)
Introduction: In the CAPITAL study, a randomized phase 3 study, wherein carboplatin plus nab-paclitaxel treatment was compared with docetaxel treatment for older patients with squamous-cell lung cancer, the former became the new standard of care for such patients. Our study aimed to evaluate whether the efficacy of second-line immune checkpoint inhibitors (ICIs) affected the primary analysis of overall survival (OS). Methods: Herein, we performed a post hoc analysis of the impact of second-line ICIs on OS, safety in each group of participants aged more than 75 years, and intracycle nab-paclitaxel skip status. Results: Patients were randomly allocated to the carboplatin plus nab-paclitaxel (nab-PC) arm (n = 95) or the docetaxel (D) arm (n = 95). Of these patients, 74 of 190 (38.9%) were transferred to ICIs for second-line treatment (nab-PC arm: 36, D arm: 38). A survival benefit was numerically observed only for patients for whom first-line therapy was terminated owing to disease progression (median OS [nab-PC arm]: with and without ICIs, 321 and 142 d, respectively; median OS [D arm]: with and without ICIs, 311 and 256 d, respectively). The OS among patients who received ICI after adverse events was similar in the two arms. In the D arm, a significantly higher frequency of grade greater than or equal to 3 adverse events was observed among patients aged more than or equal to 75 years (86.2%) than among those aged less than 75 years (65.6%, p = 0.041), including a significantly higher frequency of neutropenia (84.6% versus 62.5%, p = 0.032); no such differences were observed in the nab-PC arm. Conclusions: We found that second-line ICI treatment seemed to have a little impact on OS.